Factors related to a non‐localising technetium 99m sestamibi scan result during parathyroid adenoma imaging in primary hyperparathyroidism. (28th December 2020) - Jackson, Richard; Chew, Dylan; McClean, Simon; England, James
Abstract: Objectives: The aim of this study is to investigate factors that are associated with having a non‐localising 99m Tc‐sestamibi scan. Design: A retrospective study was performed on patients that underwent parathyroid surgery performed within a single institution between 2001 and 2018. Setting: Single tertiary centre for parathyroid surgery. Participants: 230 patients underwent surgery for primary hyperparathyroidism due to a solitary parathyroid adenoma and had preoperative 99m Tc‐sestamibi imaging. Main outcome measures: Variables including age, gender, intra‐operative location of parathyroid adenoma, adenoma weight and pre‐ and postoperative calcium and parathyroid hormone levels were investigated through univariate and multivariate analysis to identify any association with having a non‐localising (negative) 99m Tc‐sestamibi scan result. Results: Multivariate analysis identified that right‐sided adenomas ( P = .038), superior adenomas ( P = .042) and a lower preoperative PTH level ( P = .034) were all individual factors associated with having a negative 99m Tc‐sestamibi scan result. Although the weight of the adenoma was significant on univariate analysis ( P = .029), this was not demonstrated on multivariate analysis ( P = .422). Conclusion: Factors that were associated with having non‐localising 99m Tc‐sestamibi scan were right‐sided adenomas, superior adenomas and lower preoperative PTH level. Further large prospective multicentre studies are needed to further evaluate these initial findings.